A Review of the Inflammatory Chorioretinopathies: The White Dot Syndromes. (31st October 2013) - Crawford, Courtney M.; Igboeli, Okezie
Abstract : The white dot syndromes are a group of inflammatory chorioretinopathies of unknown etiology which have in common a unique and characteristic appearance of multiple yellow-white lesions affecting multiple layers of the retina, retinal pigment epithelium (RPE), choriocapillaris, and the choroid. They also have overlapping clinical features. We discuss acute retinal pigment epitheliopathy, multiple evanescent white dot syndrome, acute posterior multifocal placoid pigment epitheliopathy, multifocal choroiditis and panuveitis, acute zonal occult outer retinopathy, birdshot chorioretinopathy, and serpiginous choroidopathy. Some of these diseases are associated with a viral prodrome suggesting a possible viral/infectious etiology, while others are associated with a number of systemic processes suggesting an autoimmune etiology. We also review the presentation, evaluation/diagnosis, and treatment of these entities as well as the prognosis. Where applicable we discuss recent advancements in diagnosing and treating the white dot syndromes.